PEMAKNAAN LAFAL JAMA’A MĀLAN WA ‘ADDADAH DALAM Q.S. AL-HUMAZAH [104] : ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE - M. Rais Nasruddin; Rahma Aulia (IAT IAIN Pontianak, 2022)
This article starts from the case of cooking oil hoarding that has occurred in Indonesia recently. One of the verses of the Qur’an that relates to this problem is the second verse of sura al-Humazah in the pronunciation of jama’a malān wa ‘addadah. So the author tries to reveal the meaning behind that pronunciation. This article is a library research using Ferdinand de Saussure’s syntagmatic-paradigmatic and signifier-signified theory, and looking at the explanation of the socio-historical context of Arab society when sura al-Humazah was revealed, to find the meaning (signified) of jama’a malān wa ‘addadah (signifier). This article concludes that the meaning of jama’a malān wa ‘addadah is people who like to accumulate and calculate wealth because they are arrogant with it. So the case of cooking oil hoarding is also included in the category of jama’a malān wa ‘addadah.